Studium tepelně izolačních vlastností cementových betonů při zvýšené teplotě - Nováková, Iveta (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Diplomová práce se skládá ze dvou částí, teoretické a praktické. V teoretické části jsou uvedeny základní informace o lehkých betonech, se zaměřením na vlastnosti a využití lehkého hutného betonu s kamenivem Liapor. Dále je popsán vliv zvýšené teploty na strukturu betonu a změny chemické, mechanické a fyzikální probíhající při tepelném zatížení. Také je zhodnocena propustnost betonu a vliv polypropylenových vláken na odolnost betonu vůči zvýšeným teplotám. V praktické části je proveden návrh, výroba a zkoušky cementových betonů s využitím různých druhů kameniva (lehké kamenivo Liapor, čedič) pro zjištění jejich vlastností a vhodnosti použití při zvýšených teplotách. Je posouzen vliv zvýšené teploty na pevnost, nasákavost, tepelnou vodivost, změnu povrchové propustnosti a degradaci zkušebních desek zatěžováním dle normové teplotní křivky (ISO 834). Prováděné práce jsou pro přehlednost rozděleny do pěti etap a na konci každé etapy jsou posouzeny výsledky z naměřených hodnot. Závěrem jsou shrnuty veškeré poznatky a vyhodnocena nejvhodnější receptura včetně návrhu postupu pro další výzkum.

Master`s thesis is divided in to two parts, practical and theoretical. In theoretical part are listed basic information’s about light weight concrete, special emphasis are given to characteristic and practical application of compact light weight concrete with Liapor aggregates. In this study is described influence of high temperature on concrete structure and chemical, mechanical and physical changes, which take place during exposal to high temperatures. Further is evaluated surface permeability of concrete and addition of polypropylene fibres to concretes resistive to high temperatures. The practical part deals with design, production and testing of cement based concrete with use of different aggregates (light weight aggregates Liapor, basalt). The properties and use for applications in high temperatures is also mentioned. The influence of high temperature on strength, absorption, thermal conductivity, changes of surface permeability and degradation of testing specimens due to heat loads according to normative heat curve (ISO 834). For better transparency are experimental tests divided in to five phases and the measured values are evaluated on the end of each phase. In conclusion are resumed all knowledge’s obtained by testing and evaluated the most suitable formulation. The approach for further research is also mentioned.
Study of thermal insulation properties of cement concrete exposed to high temperature
Keywords: Lehká hutný beton s kamenivem Liapor; kamenivo čedič; zvýšená teplota; struktura betonu; součinitel tepelné vodivosti; teplotní křivka ISO 834; Light weight concrete with Liapor aggregates; basalt aggregates; high temperatures; structure of concrete; coefficient of thermal conductivity; normative heat curve (ISO 834)